The Impact of Noise Label on Beampattern and SINR of MVDR Beamformer - Suhail Najm, Shahab; Ayib Rosdi, Zainun; Izzeldin, I. Mohd; Nurul Hazlina, Noordin (International Institute of Engineers (IEE), 2016)
Minimum Variance Distortionless Response (MVDR) is basically a unity gain adaptive beamformer which is suffered from performance degradation due to the presence of interference and noise. Also, MVDR is sensitive to errors such as the steering vector errors, and the nulling level. MVDR combined with a linear antenna array (LAA) is used to acquire desired signals and suppress the interference and noise. This paper examines the impact of the noise variance label (σn2) and the number of interference sources by using Signal to Interference plus Noise Ratio (SINR) and array beampattern as two different Figure-of-Merits to measure the performance of the MVDR beamformer with a fixed number of array elements (L). The findings of this study indicate that the MVDR have successfully placed nulls in the nonlook angle with average SINR of 99.6, 49.6, 24.9 dB dB for σn2.of -50, 0, 50 dB, respectively. Also, the MVDR provides accurate majorlobe to the real user direction, even the σn2 are bigger than desired signal power. The proposed method was found to perform better than some existing techniques. Based on this analysis, the beampattern is not heavily relies on the σn2. Moreover, the SINR strongly depends on the σn2 and the number of SNOIs.